2021
DOI: 10.1007/s40122-021-00334-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analgesic Effects between Nalbuphine and Sufentanil in First-Trimester Surgical Abortion: A Randomized, Double-Blind, Controlled Trial

Abstract: Introduction: Surgical abortion is one of the commonly conducted procedures worldwide. Nevertheless, pregnant women still complain of procedural and postoperative pain despite the use of advanced anesthesia. It is vital to women's reproductive healthcare to improve postsurgical pain management to achieve the lowest level of pain. Methods: This randomized, double-blind, parallel-controlled clinical trial compared the analgesic effects between nalbuphine and sufentanil in patients who underwent first-trimester s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…These findings are also conquering with results of a similar study by Solanki et al 18 Stable hemodynamics, controlled hypotension, and decreased bleeding could be responsible for a better surgical field in Group N in our study. Intraoperative VAS pain score was lower in Group N than in Group P. 19,20 Intraoperative RSS was higher in Group N than in Group P. The findings can be explained easily by the property of propofol to reduce sympathetic activity in the body when it combines with nalbuphine (Ghali et al). 20 Although this study has compared the nalbuphine and propofol versus pentazocine and promethazine in MAC, with LA, the study was single centered.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also conquering with results of a similar study by Solanki et al 18 Stable hemodynamics, controlled hypotension, and decreased bleeding could be responsible for a better surgical field in Group N in our study. Intraoperative VAS pain score was lower in Group N than in Group P. 19,20 Intraoperative RSS was higher in Group N than in Group P. The findings can be explained easily by the property of propofol to reduce sympathetic activity in the body when it combines with nalbuphine (Ghali et al). 20 Although this study has compared the nalbuphine and propofol versus pentazocine and promethazine in MAC, with LA, the study was single centered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NAL at 0.128 mg/kg used in outpatient‐induced abortion as an intraoperative and postoperative analgesic showed a better effect compared with equivalent dose of SUF (0.128 μg/kg) 31 . Moreover, a randomized, double‐blind, controlled trial investigated the comparison of analgesic effects between NAL (0.1 mg/kg) and SUF (0.1 μg/kg) in first‐trimester surgical abortion 32 . Additionally, PCIA of NAL (100 mg) + ramosetron (0.3 mg) or SUF (100 μg) + ramosetron (0.3 mg) after cesarean section were compared with a previous study 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Pain is an inevitable complication after surgery, which will bring great suffering to patients, cause changes in endocrine and metabolic functions of patients, delay postoperative recovery, and increase medical costs [14]. Therefore, how to relieve postoperative pain has always been a hot issue for anesthetists [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nalbuphine hydrochloride (referred to as ''nalbuphine'') is a centrally acting opioid, which can activate j receptors to produce central analgesic and sedative effects; it also partially antagonizes l receptors, thereby reducing the side effects associated with activating l receptors, such as respiratory depression, nausea and vomiting, and skin itching [13]. Several studies have shown that nalbuphine has the advantages of good analgesic effect, rapid onset, long duration of action, and less incidence of adverse reactions [14]. Both nalbuphine and equivalent doses of sufentanil can provide good intraoperative and postoperative analgesia [15].…”
Section: Introductionmentioning
confidence: 99%